1974
DOI: 10.1677/joe.0.0620245
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Incidence of Mating and Copulation-Induced Ovulation After Olfactory Bulb Ablation in Female Rats

Abstract: Intact control and sham-operated rats, when given sodium pentobarbitone at 13.30 h on the day of pro-oestrus, mated (controls, 10/12; shamoperated, 13/15) that night and underwent copulation-induced ovulation. However, after removal of the olfactory bulbs only 13 out of 23 pentobarbitone-blocked rats mated. Of the mated animals only six ovulated as compared with ten in the unoperated group and ten in the sham-operated group. The incidence of ovulation in all non-mated animals was low. In addition, the bulbecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Thus a shortening of the duration of the estrous cycle was shown in female rats when they were exposed to a male rat or to the urine from animals of the same strain [1][2][3][4][5][6][7][8][9][10][11][12]. In contrast, suppression of the ol factory signals by removal of the olfactory bulbs resulted in delayed onset of sexual maturity [14] or in a reduced num ber of animals ovulating after mating [11]. …”
mentioning
confidence: 99%
“…Thus a shortening of the duration of the estrous cycle was shown in female rats when they were exposed to a male rat or to the urine from animals of the same strain [1][2][3][4][5][6][7][8][9][10][11][12]. In contrast, suppression of the ol factory signals by removal of the olfactory bulbs resulted in delayed onset of sexual maturity [14] or in a reduced num ber of animals ovulating after mating [11]. …”
mentioning
confidence: 99%
“…For example, the olfactory system has been shown to be important in mediating copulation-induced ovulation in pentobarbitone-blocked pro-oestrous rats (Curry, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on female rats by Kling (1964) showed that there was a slight reduction in mating capacity and gonadal weights after either bilateral or unilateral olfactory bulb lesions during infancy. Curry (1974) also reported that bulbectomized female rats mated less frequently than normal females. Orbach and Kling (1966), however, found no significant decreases in mating after peripheral olfactory impairment during infancy.…”
Section: Procedures For Producing Olfactory Deficitmentioning
confidence: 94%